The critical success factors of e-procurement adoption - Vijayaseri, Nithianathan (2014)
E-Procurement is electronic used system for making the purchases through online by a single click. Some of the companies all over the world implement E-Procurement and succeed while some companies was failed. There are two main objectives of this research study; To identity the critical success factors influencing the success of E Procurement and at the same time to establish the challenges that face E-Procurement adoption in Top Glove Sdn. Bhd. With the rapid changes in dynamic society, organizations must adopt and adapt with the new paperless procurement process to be on par with the competitors. This research is a qualitative research study and it involves interview session with expert and experience staffs particularly from a manufacturing industry which produces its own products. Information and data are some first and secondary data which were collected and compiled from the particular organization. At the end of the research, it is indeed the embracing of new procurement process has increased the performance of procurement in the industry. Organizations are able to minimize cost, supply chain players, on the other hand, are able to share information at real time to avoid future production line down which will cost much on the changeover. The longer the changeover duration in production line, the higher the loss to the organization. In addition, the paperless way of work flow will reduce bureaucracy which means it will result in less time consumption. In a nutshell, the adoption of E-Procurement in manufacturing industry will exert higher procurement performance. Managers, buyers, planners, schedulers, suppliers, and master planners are able to foster stronger bond and understanding to achieve the common ultimate goals and aims.